New Economic Paradigm: Universal Basic Income - Sey, Nurbay; İşler, Çağrı (Journal of Applied And Theoretical Social Sciences, 2024)
With the rapid increase in technology in production, the idea that robots will take away people's jobs and that this will lead to a major social problem has started to gain prominence. In such a situation, there will be a need for both income sufficient to ensure people's basic livelihoods and the preservation of social peace. At this point, the idea of a universal basic income comes to the fore. Universal basic income can be defined as the amount of money paid unconditionally and regularly to every individual in society. In this study, the theory of universal basic income is examined from many aspects. In this context, the scope and motivation of universal basic income are presented, and the advantages that basic income would provide for both workers and capital owners are evaluated separately. Additionally, within the scope of this study, it is demonstrated that it is possible to finance basic income by considering the social expenditures made by states. The study also evaluates the criticisms of basic income and the responses to these criticisms. Furthermore, the pilot implementations of universal basic income and their results are analyzed. In the conclusion section of the study, it is reached that basic income is consistent but its simultaneous implementation on a universal level is not yet possible in its current form.